Dynamic relationship between gut microbiota and post-necrotizing pancreatitis: insights from a multi-stage 16S rRNA sequencing study - Lu, Jiongdi; Wang, Zhe; Cao, Feng; Li, Jia; Ji, Guofeng; Li, Fei (Frontiers in Pharmacology, 2025)
BackgroundAcute pancreatitis (AP) is a common digestive disorder, with necrotizing pancreatitis (NP) occurring in 20% of cases. Long-term complications can include pancreatic exocrine and endocrine insufficiency, with gut microbiota (GM) playing a significant role in pancreatic diseases. Although previous studies have established a connection between gut microbiota dysbiosis and the onset of necrotizing pancreatitis, the composition of GM in patients who have experienced post-NP post-necrotizing pancreatitis remains largely unexamined.MethodsWe conducted a single-center, prospective, long-term follow-up study of 88 participants, including 68 NP patients and 20 healthy controls. NP patients were divided into NP (onset-NP) and PNP groups based on disease progression. Gut microbial diversity and composition were assessed using 16S rRNA sequencing, followed by bioinformatic analyses such as Alpha and Beta diversity metrics, linear discriminant analysis effect size (LEfSe), and functional pathway predictions. Clinical data were correlated with GM profiles to evaluate associations.Results29.5% and 19.1% of NP patients progressed to pancreatic endocrine and exocrine insufficiency, respectively. Alpha and Beta diversity analyses revealed significantly lower microbial diversity in NP and PNP groups. Dysbiosis was characterized by a reduction in beneficial bacteria such as Faecalibacterium prausnitzii and Bacteroidaceae, and an increase in opportunistic pathogens such as Streptococcus and Enterobacter. Functional prediction suggested disruptions in cellular processes, including apoptosis and necroptosis, and links to pathways associated with inflammatory and metabolic diseases. Correlation analyses demonstrated significant associations between GM alterations and clinical markers of inflammation, such as IL-6, C-reactive protein (CRP), and Procalcitonin (PCT).ConclusionOur findings highlight distinct GM profiles in NP and PNP patients compared to healthy controls, with partial recovery of beneficial flora in PNP patients. The study underscores the role of GM dysbiosis in NP progression and long-term outcomes, offering insights into potential therapeutic targets and strategies to improve patient management and quality of life. Future studies should explore multicenter validations and the mechanisms linking GM alterations to clinical outcomes.